Experimental Study on the Effect of Compaction Work and Defect on the Strength of Soil-Rock Mixture Subgrade - Xin Yan; Wei Zhan; Zhi Hu; Yiqiang Yu; Danqiang Xiao (Advances in Materials Science and Engineering)
Soil-rock mixture is a common filling material for earth dam and subgrade. In this study, research concerned on the evolution law of engineering characteristics of soil-rock mixture under different factors and the effect of defect on subgrade strength, and geotechnical tests were carried out to analyze the influence of different factors on engineering characteristics of soil-rock mixture in the study, and the physical model was carried out to analyze the effect of different compaction works on the resilient modulus, and the influence of defect on the strength was explored by manually preset loose body. The test results showed that (1) when the soil-rock mixture was graded, P = 78, the moisture content was 14%, and the engineering characteristics were optimal; (2) there was a positive correlation between compaction times and resilient modulus, and the stress transferred from the subgrade to soil was linearly distributed under the good condition of compactness; and (3) the existence of loose body not only reduces the modulus of resilience but also affects the stress transfer; the larger the loose body, the lower the resilient modulus and the greater the stress transfer.